Hide and seek, nuts to eat - Gold, Tracy C. (Sourcebooks eXplore, 2023)
"Follow along as one squirrel hides seeds, nuts, and berries that her neighbors will seek later! Scientific back matter about squirrel hoarding and different squirrels from around the world included"--